Comparação entre a aplicação do coagulante natural Moringa oleifera e do coagulante químico sulfato de alumínio no tratamento de água com diferentes níveis de turbidez - Pereira, Edilaine Regina (2015)
The developed study aimed performing the application of aluminum sulfate (chemical coagulant) and Moringa oleifera (natural coagulant) in water samples to verify the removal of color and turbidity, as well as verify pH behavior throughout the analysis. For this purpose, samples of water with turbidity of 50, 100 and 150 nephelometric turbidity units (NTU) were prepared and used Jar Test for various time intervals in order to perform the coagulation and flocculation tests. It was observed a constant pH behavior with no significant variations when comparing the initial sample and after the application of the coagulants. On removal of turbidity of the solution Moringa oleifera was more efficient, by reducing 77.56%, on the other hand aluminum sulfate reduced only 28.22%. For the color was obtained satisfactory results from both coagulant in which the best values were 99.47 % for aluminum sulfate and 94.01% for the Moringa oleifera, these results were acquire for the turbidity of 100 NTU .